Aph-1 Associates Directly with Full-length and C-terminal Fragments of γ-Secretase Substrates - Chen, Allen C. (American Society for Biochemistry and Molecular Biology, 2010)
γ-Secretase is a ubiquitous, multiprotein enzyme composed of presenilin, nicastrin, Aph-1, and Pen-2. It mediates the intramembrane proteolysis of many type 1 proteins, plays an essential role in numerous signaling pathways, and helps drive the pathogenesis of Alzheimer disease by excising the hydrophobic, aggregation-prone amyloid β-peptide from the β-amyloid precursor protein. A central unresolved question is how its many substrates bind and enter the γ-secretase complex. Here, we provide evidence that both the β-amyloid precursor protein holoprotein and its C-terminal fragments, the immediate substrates of γ-secretase, can associate with Aph-1 at overexpressed as well as endogenous protein levels. This association was observed using bi-directional co-immunoprecipitation in multiple systems and detergent conditions, and an β-amyloid precursor protein-Aph-1 complex was specifically isolated following in situ cross-linking in living cells. In addition, another endogenous canonical γ-substrate, Jagged, showed association of both its full-length and C-terminal fragment forms with Aph-1. We were also able to demonstrate that this interaction with substrates was conserved across the multiple isoforms of Aph-1 (β, αS, and αL), as they were all able to bind β-amyloid precursor protein with similar affinity. Finally, two highly conserved intramembrane histidines (His-171 and His-197) within Aph-1, which were recently shown to be important for γ-secretase activity, are required for efficient binding of substrates. Taken together, our data suggest a dominant role for Aph-1 in interacting with γ-secretase substrates prior to their processing by the proteolytic complex.